LMO3 downregulation in PCa: A prospective biomarker associated with immune infiltration - Xu, Wenchao; Sun, Taotao; Wang, Jiaxin; Li, Hao; Chen, Bingliang; Zhou, Yingjian; Wang, Tao; Wang, Shaogang; Liu, Jihong; Jiang, Hongyang (Frontiers in Genetics, 2022)
Prostate cancer is the third leading cause of new cancer cases and the second most common tumor type in men globally. LMO3 has been stated to play a vital role in some cancers; however, the prognostic value of LMO3 in PCa remains vague. Here, we utilized various web databases to elucidate in detail the prognostic value and molecular functions of LMO3 in PCa. LMO3 expression was significantly decreased in PCa. Low LMO3 expression was associated with gender, age, and TNM grade and predicted a poor prognosis in PCa patients. Functional enrichment analysis suggested that LMO3 is engaged in the extracellular matrix and immune response. Moreover, LMO3 was positively correlated with immune infiltration levels and numerous immune markers. LMO3 may function as a prospective biomarker of immune infiltration in PCa.